The Curious Case of Lip Tongue Fusion: A Consequence of Suboptimal Oral Care. (8th November 2022) - Xu, Jimmy; Biyani, Prateek; Rajkumar, Andrew; Orr, Robert
Abstract : Oral care is an often difficult and an unappreciated part of hospital life. Patients who are unable to provide their own care rely on assistance from hospital personnel. Most sequelae from suboptimal oral care often present over months if not years, in the form of dental caries and periodontal disease. We present an exception, where a 66-year-old patient who experienced widespread ulceration and necrosis from Capnocytophaga -related sepsis received suboptimal oral care, resulting in their tongue being fused to their lip. This was later divided by the oral and maxillofacial team resulting in restoration of full function. Future cases can be avoided in patients with similar symptoms, such as Stevens-Johnson syndrome or erythema multiforme, if rigorous oral care can be provided.